Kajian keberadaan ikan sidat Anguilla marmorrata di Muara Sungai Wae Randang Desa Nanga Mbaur Kabupaten Manggarai Timur pada bulan November-Desember - Harkai, Eufrasia Desriyani; Sunadji, Sunadji; Lukas, Ade Yulita Hesti (Jurnal Aquatik, 2024)
Wae Randang is one of the rivers that flows in Ngana Mbaur Village and directly empties into the sea. This river has the potential for eel population, because its location is in accordance with the natural habitat of eel fish. Therefore, it is necessary to conduct research to assess the presence of eel Anguila marmorata in Wae Randang River, especially from November to December. The purpose of this study was to determine the length, weight, and diameter of A. marmorata eels found in certain periods in the river. The research was conducted from November to December 2022, with descriptive data analysis and presented in the form of figures and tables. In the study obtained as many as 11 eels A. marmorata caught during November to December. The fish had a total length of 30-52 cm, total weight of 48-323 g, anal length 17-30 g, dorsal length 19-42 g, body diameter 6-12 g, and head diameter 5-9 cm. Based on the length and weight of the recorded eels, the fish were in the elver and yellow eel stadia. Keywords: Eel, potential, study, Wae Randang